Prilaku Personal Hygiene Remaja Putri Pada Saat Menstruasi - Dahniar Dahlan (Unit Publikasi Ilmiah Perkumpulan Intelektual Madani Indonesia, 2021)
Menstrual personal hygiene is a component of the personal hygiene plays an important role in determining the health status, particulary protected from infection reproduction organ. Due to the lack of understanding of personal hygiene genetalia during menstruation is occurance of reproductive health disorders such as, vaginal discharge, urinary tract infection, pelvic inflammatory disease and the possibility of cervical cancer. One cause of fungal and bacterial infections in women is the lack of personal hygiene behavior during menstruation and lazy to change pads. The purpose of this research was to determine the relationship of knowledge, providing information with menstrual personal hygiene teenage girl in SMP Negeri 4 Baubau. The method of this research was analytic survey with cross sectional design. The population in this reseach were consist of teenage girl class VII, VIII dan IX who had menstruated, as many as 41 people and the entire population was sampled. The analysis used was univariate and bivariate with the Statistical test used chi-square test at the 95% confidence level (?=0,05). The result showed that there was significant relationship between Knowledge (pvalue=0,001 <0,05), providing information (p- value=0,002<0,05) with menstrual personal hygiene teenage girl. It was expected that in the future teenage girl could maintain good behaviour during menstruation and continue to increase knowledge about personal hygiene during menstruation.